Evaluasi Keselamatan dan Kesehatan Kerja (K3) pada Praktek Instalasi Penerangan Listrik di SMK Muhammadiyah 1 Padang - As'ari, Abul Hasan; Hambali, Hambali (Universitas Negeri Padang, 2023)
This research was motivated by the work attitudes of students in implementing K3 when practice in the practicum workshop was not going well. Students ignore the potential dangers of using Personal Protective Equipment (PPE), students who use practical equipment often experience injuries to students' hands or scratches on work objects due to improper use. This research aims to determine the evaluation of occupational safety and health (K3) in the practice of installing electrical lighting at SMK Muhammadiyah 1 Padang. The population in this study were all students of Electrical Lighting Installation Practice at SMK Muhammadiyah 1 Padang class XI and XII at SMK Muhammadiyah 1 Padang. This research is quantitative descriptive. The sampling technique in this research is total sampling. The analysis of this research is descriptive. In this research, the instruments used include questionnaires. Questionnaires were used in this research to collect data. In this study, the percentage score technique was used. The percentage score is used to determine the category of research results for each point and its indicators, variables and subvariables. Based on the percentage score, the average score for the occupational safety and health (K3) evaluation variable in the practice of installing electrical lighting at SMK Muhammadiyah 1 Padang is obtained, which consists of 30 questions, where the average score is 4 with a Respondent Achievement Level (TCR) of 85% . This shows that the evaluation of occupational safety and health (K3) in the practice of electrical lighting installation at SMK Muhammadiyah 1 Padang is in the Very Good category.